2021
DOI: 10.7150/ijms.59171
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy for intervertebral disc degeneration: inhibiting apoptosis is a promising treatment strategy

Abstract: Intervertebral disc (IVD) degeneration (IDD) is a multifactorial pathological process associated with low back pain (LBP). The pathogenesis is complicated, and the main pathological changes are IVD cell apoptosis and extracellular matrix (ECM) degradation. Apoptotic cell loss leads to ECM degradation, which plays an essential role in IDD pathogenesis. Apoptosis regulation may be a potential attractive therapeutic strategy for IDD. Previous studies have shown that IVD cell apoptosis is mainly induced by the dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 115 publications
0
33
0
Order By: Relevance
“…The Fas death receptor is a therapeutic target for inhibiting apoptosis via the extrinsic pathway. A previous study has shown a reduction in apoptosis and improved annulus fibrosus cell proliferation with Fas-siRNA in a serum starvation model [99]. Bim, a member of the BH3 subfamily of the Bcl-2 family is also targeted for inhibiting apoptosis.…”
Section: Small Interfering Rna (Sirna)mentioning
confidence: 99%
“…The Fas death receptor is a therapeutic target for inhibiting apoptosis via the extrinsic pathway. A previous study has shown a reduction in apoptosis and improved annulus fibrosus cell proliferation with Fas-siRNA in a serum starvation model [99]. Bim, a member of the BH3 subfamily of the Bcl-2 family is also targeted for inhibiting apoptosis.…”
Section: Small Interfering Rna (Sirna)mentioning
confidence: 99%
“…It is widely believed that IVD apoptosis and inflammatory response play important roles in the IVDD process. By studying the mechanisms of apoptosis and inflammatory response, targeting and regulating the specific mediating pathways provide hope for the treatment of IVDD [ 18 , 19 ]. Many studies have found that the caspase family is involved in the apoptosis and inflammatory response pathways and plays a crucial role [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Wnt/β-catenin pathway activity plays a vital role in IVDD, and inhibition of the pathway by targeted therapy is an effective treatment. 23 Periostin (POSTN), an extracellular matrix (ECM) protein, is expressed in healthy tissues and has been used as a biomarker because it is aberrantly expressed in many diseases, such as asthma, 24,25 osteoarthritis, 26,27 and tumors. 28,29 POSTN is also expressed in IVDs and to be upregulated in IVDD.…”
Section: Introductionmentioning
confidence: 99%